Environmental conditions shaping star formation: the Carina Nebula. Issue 2 (3rd December 2018) - Contreras, Y; Rebolledo, D; Breen, S L; Green, A J; Burton, M G
Abstract: Using the Mopra telescope, we have targeted 61 regions in the Carina Nebula, covering an area of 1.5 deg 2, of bright and compact 870 μ m dust continuum emission for molecular line emission from a host of 16 spectral lines at 3 mm, including several dense gas tracers. We found that the clumps detected in Carina in general have in average higher temperatures (27 K compared to 21 K), and lower masses (214 M⊙ compared to 508 M⊙ ) than clumps located at a similar distance to us in the Galactic plane. We compare the properties of the molecular line emission of these clumps with the MALT90 survey, finding that the detection rates of the molecular lines are similar to MALT90 clumps that are classified as photodissociation regions. However, most of the clumps located within 10 arcmin of η Carina have little molecular line emission detected in our observations. Given the lack of maser detection in the Carina region, we also compared the properties of the clumps in Carina to those of Galactic clumps associated with 6.7-GHz methanol masers. We found that the clumps in Carina are warmer, less massive, and show less emission from the four most commonly detected molecules, HCO +, N2 H +, HCN, and HNC, compared to clumps associated with masers in the Galactic Plane. Overall our results are consistent with the scenario in which the high radiation field of η Carina is dramatically affecting its local environment, and therefore the chemical composition of the dense clumps.